Life-Threatening Adenovirus Infections in the Setting of the Immunocompromised Allogeneic Stem Cell Transplant Patients - Cedar J. Fowler; Jennifer Dunlap; Darcy Troyer; Peter Stenzel; Elliot Epner; Richard T. Maziarz (Advances in Hematology)
A single institution case series of adenovirus infections after allogeneic hematopoietic stem cell transplantation is presented to highlight the consideration for adenovirus infections as an etiology in patients with rapid hepatic or other sudden organ deterioration in the setting of apparent GVHD stabilization. The series also highlights that survival is limited with these infections often due in part to concomitant opportunistic infections. In addition, the pathophysiological events, such as GVHD and hepatic dysfunction, may complicate the clinical picture and delay therapy of an opportunistic infection. This is particularly true for adenoviral infections as they also have a distinct clinical picture in immunocompromised patients when compared to immune competent patients. Adenovirus infections also have the additional challenge that its treatment, cidofovir, has associated toxicities that can delay its administration. Recent developments has yielded an assay that can be used in the early detection and for serial determinations of adenovirus in patients with advanced GVHD, as well as a new therapeutic agent currently undergoing clinical trials.